Improving contractors’ practices of Industrialised Building System (IBS) implementation in construction industry - Ali Al-Shami, Mohammed Hamid (2019)
Malaysian construction industry plays an important role in creating wealth for the country as developing social, economic and infrastructure. The government has adopted industrialised building systems (IBS) since the 1960s and has made significant efforts in this area. It aims to achieve several improvements within the industry, such as higher productivity levels and better quality construction products. The main reason for delay the completion of construction projects was due to poor practice of contractors. Lack of experience, financial problems, lack of technical knowledge and lack of skilled labour are very important barriers to successful IBS implementation. The objectives of this research were to investigate current contractors’ practices of IBS implementation in construction industry, to identify influencing factors for contractors’ practices of IBS implementation in construction projects and to recommend ways to improve contractors’ practices of IBS implementation in construction industry. The research was take place in Johor Bahru the capital of Johor state where various development and construction activities are currently on going. Quantitative method was used by distribution of questionnaire that is designed based on the research objectives, data collected was analysed using the Statistical Package for the Social Science 22.0 software to carry out the research aims. Target respondents were the construction industry player, namely Grade 7 (G7) contractors. Contractors G7 was chosen because they are the main contractor with unlimited tendering abilities and they are involved with wide practice of IBS adaption. The study reveals that there are some problems faced by contractors in their practices of IBS implementation such as low productivity, management aspects and financial problems. Therefore, training to labour, IBS instruction guideline and improving finance and procurement mechanism is the top recommended factors to improve contractors’ practices of IBS implementation for more IBS adaption success.